Nursing of a patient with type 2 diabetes mellitus complicated with invasive pulmonary aspergillosis resulting in the formation of a cavity in the upper lobe of the right lung causing hemoptysis (1例2型糖尿病合并侵袭性肺曲霉菌病致右肺上叶空洞形成致大咯血患者的护理体会) - TIAN Haitong (田海彤); YU Xiaojie (于潇杰); LIU Zhenmei (刘振梅); DU Chunmei (杜春梅); XING Yuejiao (邢月娇); LIN Xiaomeng (林晓萌); JIANG Wenjie (姜文杰); WANG Cong (王琮); ZHANG Mengjie (张梦婕); LU Kexin (陆可欣); ZHAO Yanan (赵亚楠) (Association of Integrative Nursing, 2023)
This paper summarized the nursing of a patient with type 2 diabetes mellitus complicated with invasive pulmonary aspergillosis resulting in the formation of a cavity in the upper lobe of the right lung causing hemoptysis. Nurses had closely observe the changes in the patient's condition and carried out comprehensive interventions including hemoptysis care, dietary care, disinfection and isolation, cough and sputum production and oxygen therapy care, Traditional Chinese Medicine nursing, psychological care and health education. Efforts were made to reduce the risk of hemoptysis, control the blood glucose, improve immunity and quality of life of the patient. (本文总结1例2型糖尿病合并侵袭性肺曲霉菌病导致右肺上叶空洞形成致大咯血患者的护理的经验。患入院后密切观察病情变化, 给予咯血护理、饮食护理、消毒隔离、咳嗽咳痰及氧疗护理、中医护理、心理护理以及健康宣教, 降低患者咯血风险, 积极控制血糖, 增强机体抵抗力, 提高生活质量。)